Employee’s Soft Skills as A Successful Way to Achieve Personal Branding: Scientific Literature Review - Kusdinar, Felicia Azzahra; Mayuni, Ilza; Khumaeroh, Indri Deviriani (Journal of Social Science, 2023)
21st century era has strong competition in the world industry. Competition can be overcome by having self-ability. Soft skills are the main key in the world of industry that can be developed from an early age in school. Soft skills will help someone in pursuing a career in the future. Thus, this paper aims to analyze the knowledge of employee soft skills needed in the 21st century era to achieve personal branding. The data were taken through a literature review using several journals. By applying a strictly reproducible process, the method used was library research with analyzing peer-reviewed journal articles on soft skills needed in 21st century. This paper utilized scientific journals that focused on soft skills employee in 21st century keyword and personal branding for career keyword. The finding showed the core of employee skills were communication skill, critical thinking skill, and problem-solving skill. These core soft skills would lead to another soft skill, like creativity skill, negotiation, and decision- making skill. They could be formed and practiced by schools’ learning through group discussion, debate, writing report, and presentation. Thus, through the implementation of core soft skills, personal branding would follow automatically as self- characteristic. This research made a significant contribution by providing an updated and convincing summary that could be built and applied in individuals. Thus, it has potential for future research or practice.